DEVELOPMENT AND VALIDATION OF NOVEL INDEL MARKERS LINKED TO LOW LIGHT TOLERANCE TRAITS IN RICE (Oryza sativa L.) USING F2 MAPPING POPULATION (Applied Biological Research, 2026)
Light intensity is a key factor affecting the growth and yield of rice (Oryza sativaL.). Thisstudy evaluated 200 F2 progenies from a ‘GAR-2 × Danteshwari’ cross under 30% shading at ICAR-NEH Region, Umiam, Meghalaya (India) to assess low light tolerance. The experiment was conducted in an augmented design with six standard checks (Swarnaprabha, IR8, Shah Sarang, Swarna, GAR-2, and Danteshwari), and the data was recorded for 10 agronomic traits related to growth and yield parameters. Phenotypic variability, heritability, and genetic advance were estimated, followed by marker polymorphism and marker-trait association analysis using known SSR markers and newly developed InDel markers. Significant variations were observed in seed yield plant-1(SYPP) (p ≤ 0.05) and traits such as plant height (PH), days to flowering (DTF), days to maturity (DTM), days to harvest (DTH), number of tillers (NOT), number of effective tillers (NOET), spikelet fertility (SF), biomass (BIO), and 100-seed weight (HSW) (p ≤ 0.01). High heritability and genetic advance for DTH, DTM, HSW, NOT, PH, and SF indicated additive gene action. Marker analysis revealed polymorphisms in four markers: ‘LLG4-1’, ‘LLG4- 2’, ‘HvSSR02-44’, and ‘HvSSR09-45’. Marker-trait association identified ‘HvSSR09-45’ to be significantly associated with seven traits (NOT, PH, DTF, DTM, DTH, BIO, & HSW), HvSSR02-44 with 2 traits (PH & HSW), and ‘LLG4-1’ with single trait (SYPP). These markers can be effectively utilized in marker-assisted selection in developing low light-tolerant rice varieties.
Keywords: Danteshwari, F2 population, GAR-2, low light tolerance, rice